FENOMENA KOMUNIKASI KELUARGA DALAM KESUKSESAN TIMNAS SEPAK BOLA MAROKO PADA PIALA DUNIA 2022 DI QATAR - Rina Raflina (Bajang Institute, 2023)
The progress of the Morocco national team at the 2022 World Cup in Qatar exceeded the expectations of many parties. Morocco looks amazing big European teams. Morocco's impressive performance since the group stage made them the first representatives from the African continent to reach the semifinals. The presence of parents and families of the Moroccan national team players is one of the keys to every victory for the Moroccan team. The direct presence of the family at the stadium to provide support and prayers is the spirit for the Moroccan team when they compete. Parents work together to support their children in the field. so that the cohesiveness of the Moroccan team is increasingly visible both outside the field and outside the match field. The research method used is a qualitative research method with a literature study approach.